The Benefits and Costs of Newer Drugs: Evidence from the 1996 Medical Expenditure Panel Survey - Frank Lichtenberg (Center for Economic Studies and ifo Institute (CESifo), 2000)
The nation's spending for prescription drugs has grown dramatically in recent years. Previous studies have shown that the replacement of older drugs by newer, more expensive, drugs is the single most important reason for this increase, but they did not measure how much of the difference between new and old drug prices reflects changes in quality as better, newer drugs replace older, less effective medications. In this paper we analyze data from the 1996 Medical Expenditure Panel Survey (MEPS) to provide evidence about the effect of drug age on mortality, morbidity, and total medical expenditure, controlling for sex, age, education, race, income, insurance status, who paid for the drug, the condition for which the drug was prescribed, how long the person has had the condition, and the number of medical conditions reported by the person. The results provide strong support for the hypothesis that the replacement of older by newer drugs results in reductions in mortality, morbidity, and total medical expenditure. People consuming new drugs were significantly less likely to experience work-loss days and to die by the end of the survey than people consuming older drugs. The estimates indicate that reductions in drug age tend to reduce all types of non-drug medical expenditure, although the reduction in inpatient expenditure is by far the largest. Reducing the age of the drug results in a substantial net reduction in the total cost of treating the condition. Allowing people to use only generic drugs would increase total treatment costs, not reduce them, and would lead to worse outcomes.
Keywords: 330